2014
DOI: 10.3389/fcimb.2014.00153
|View full text |Cite
|
Sign up to set email alerts
|

Glycan analysis of Fonsecaea monophora from clinical and environmental origins reveals different structural profile and human antigenic response

Abstract: Dematiaceous fungi constitute a large and heterogeneous group, characterized by having a dark pigment, the dihydroxynaftalen melanin—DHN, inside their cell walls. In nature they are found mainly as soil microbiota or decomposing organic matter, and are spread in tropical and subtropical regions. The fungus Fonsecaea monophora causes chromoblastomycosis in humans, and possesses essential mechanisms that may enhance pathogenicity, proliferation and dissemination inside the host. Glycoconjugates confer important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…Therefore, considering the available data on antigens from CBM etiologic agents and their interaction with host cells, we proposed a possible mechanism of infection and the spread of fungi in host tissues (Figure 3). Possibly, ectophosphatase, as well as other pathogen-associated molecular markers [114,115], binds to the surface of the host cell, and in the intracellular environment, melanin suppresses reactive oxygen and nitrogen species, allowing fungal survival. Melanin may suppress the process of phagocytosis, and extracellular fungi, through the action of aspartate peptidase, are able to spread through tissues, ensuring parasite survival.…”
Section: Modulation Of Host Cells By Fungi and Fungi-derived Antigensmentioning
confidence: 99%
“…Therefore, considering the available data on antigens from CBM etiologic agents and their interaction with host cells, we proposed a possible mechanism of infection and the spread of fungi in host tissues (Figure 3). Possibly, ectophosphatase, as well as other pathogen-associated molecular markers [114,115], binds to the surface of the host cell, and in the intracellular environment, melanin suppresses reactive oxygen and nitrogen species, allowing fungal survival. Melanin may suppress the process of phagocytosis, and extracellular fungi, through the action of aspartate peptidase, are able to spread through tissues, ensuring parasite survival.…”
Section: Modulation Of Host Cells By Fungi and Fungi-derived Antigensmentioning
confidence: 99%
“…Burjack et al ( 2014 ) demonstrated a structural diversity of the polysacharides from Fonsecae monophora isolated from clinical and environmental origins.…”
mentioning
confidence: 99%